Efeito do selênio e vitamina E sobre o hemograma, proteínograma e metabolismo oxidativo de cordeiros infectados experimentalmente pelo Haemonchus contortus - Nicolodi, Paula Rocha Sampaio Juchem (2008)
The present study describes the evaluation of the effect of supplementation with selenium and vitamin E on the hemogram and protein and oxidative profiles of lambs experimentally infected with Haemonchus contortus (HC). Thirty female lambs were divided into four groups as follows: G1 (n = 10): infected animals; G2 (n =10): infected and supplemented; G3 (n = 5): control; G4 (n = 5): non-infected and supplemented. Groups 1 and 2 received 500 HC larvae (L3) orally for a period of 20 days, with 2-day intervals between doses. Supplementation in groups 2 and 4 was performed on day zero by injecting 0.1 mg kg-1 of sodium selenite (1.67%) and 2,000 IU vitamin E through the intramuscular (IM) route. Vitamin E alone was injected once again on day 30. In addition to blood collections for performing the hemograms, the numbers of eggs per grams of feces (EPG) were also determined. Considering the number of erythrocytes, volume of globular proteins, hemoglobin level, total leukocytes and lymphocytes, the main differences were observed when the parasitized groups were compared to the supplemented, non-parasitized group, the latter exhibiting higher values. It is concluded that supplementation of lambs with vitamin E and selenium has no influence on their erythrogram when they are parasitized with HC. The leukogram showed higher segmented neutrophil numbers in the supplemented groups. On the other hand, vitamin E and selenium increased hematological parameters in animals not infected with HC. In considering the levels of total proteins, albumin, beta and gamma globulins, the main differences were observed when the parasitized groups were compared to the supplemented, non-infected group, the latter exhibiting higher values. It is concluded that supplementation of lambs with vitamin E and selenium has no influence on their blood protein levels when they are parasitized with HC. The non-parasitized, supplemented animals sustained better glutathione peroxidase (GSH-Px) values up to the 60th day of the experiment. No oxidative stress state took place since an increase in GSH-Px levels exerted a compensatory effect when thiobarbituric acid reactive substances (TBARS) levels rose.